Analisis kebutuhan informasi mahasiswa fakultas hukum di Universitas Lancang Kuning dalam mendukung proses belajar - Riki Dinul Ramadhan; Astin Yendani; Wirdatul Khusna; Vita Amelia (FPPTI Jawa Tengah, 2025)
This study aims to analyze the information needs of law students in learning processes, focusing on identifying characteristics of information needs, types of required information sources, information seeking behavior patterns, and encountered obstacles. Using qualitative research methods through direct interviews with 20 law faculty students of Lancang Kuning University, semesters 2, 4, and 6, which were conducted in June 2025. The findings reveal that law students have multidimensional information needs encompassing academic aspects for coursework, contextual needs for current legal issues, and practical requirements for extracurricular activities. Students employ a hierarchical search strategy starting from internal campus sources then expanding to external sources, utilizing both traditional and digital media combinations. The research demonstrates that law students' information seeking behavior has adapted to technological developments, yet still faces significant challenges in understanding legal terminology, accessing quality sources, and information validation. The study provides valuable insights for educational institutions to design appropriate library services and information infrastructure, enhances student awareness of information literacy importance, and offers input for educational technology developers to create more user-friendly and comprehensive legal learning platforms. Recommendations include developing integrated information literacy programs in curriculum, improving access to legal databases and electronic journals, and establishing strategic collaborations between institutions, libraries, and technology providers to create optimal information ecosystems supporting academic needs.